Efficacy of an antibiotic loaded ceramic-based bone graft substitute for the treatment of infected non-unions - Freischmidt, Holger; Armbruster, Jonas; Rothhaas, Catharina; Titze, Nadine; Gühring, Thorsten; Nurjadi, Dennis; Kretzer, Jan Philippe; Schmidmaier, Gerhard; Grützner, Paul Alfred; Helbig, Lars (Biomedicines, 2022)
The treatment of non-unions is often complicated by segmental bone defects and bacterial colonization. Because of the limited availability of autologous bone grafts, tissue engineering focuses on antibiotic-loaded bone graft substitutes. HACaS+G is a resorbable calcium sulphate-hydroxyapatite loaded with gentamicin. The osteoinductive, osteoconductive, and anti-infective effect of HACaS+G has already been demonstrated in clinical studies on patients with chronic osteomyelitis. However, especially for the treatment of infected non-unions with segmental bone defects by HACaS+G, reliable clinical testing is difficult and sufficient experimental data are lacking. We used an already established sequential animal model in infected and non-infected rat femora to investigate the osteoinductive, osteoconductive, and anti-infective efficacy of HACaS+G for the treatment of infected non-unions. In biomechanical testing, bone consolidation could not be observed under infected and non-infected conditions. Only a prophylactic effect against infections, but no eradication, could be verified in the microbiological analysis. Using µ-CT scans and histology, osteoinduction was detected in both the infected and non-infected bone, whereas osteoconduction occurred only in the non-infected setting. Our data showed that HACaS+G is osteoinductive, but does not have added benefits in infected non-unions in terms of osteoconduction and mechanical bone stability, especially in those with segmental bone defects.